The Influence of Exercise Model Using Video Media on Swimming Grabstart Skills for Deaf Children - Anggri Dwi Nata; Hilda Oktri Yeni; Fadli Surahman; Rusdi (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The main problem of the research is the low mastery of the skills to start swimming deaf children. The purpose of this study was to determine the effect of the exercise model using video media on swimming grabstart skills in deaf children.Subjects were 40 deaf children consisting of 20 experimental groups and 20 control groups. Data collection was carried out by conducting initial tests to grabstart swimming skills, practice (training models using video media) and final tests of grabstart swimming skills. Data analysis and hypothesis testing using comparative analysis techniques using the Dependent sample t-test, namely Paired sample t-test and Independent sample t-test, namely t-Test: Two-Sample Assuming Equal Variances with a significant level α = 0.05Based on the results of the study it can be concluded that: 1) There is an effect of the exercise model using video media on swimming grabstart skills in deaf children from an average value of 51.05 to 64.94 with Tcount = 14.93> Ttable = 2.10, 2 ) There is an influence of the control group on swimming grabstart skills in deaf children from an average value of 47.89 to 52.69 with Tcount = 4.47> Ttable = 2.10. 3) There is a difference between the effect of the exercise model using video media with a control group with Tcount = 3.82> Ttable = 2.02.